Incompatible Strategic Cultures Limit Russian-Chinese Strategic Cooperation in the Arctic - Jørgen Staun; Camilla T. N. Sørensen (Scandinavian Journal of Military Studies, 2023)
Russia’s full-blown invasion of Ukraine in February 2022 has led to concern about the implications for Arctic governance and stability. The Arctic Council has been temporarily suspended and the security tension between Russia and the seven other Western Arctic states has intensified. A more isolated Russia under Western sanctions leans even more towards the East, where China, especially, figures as an attractive strategic partner. In this article, we set out to examine the prospects for Russian-Chinese strategic cooperation in the Arctic. We introduce a social constructivist perspective highlighting how strategic culture may serve as a lens through which to analyse developments in states’ strategies – specifically their ends, ways and means. Applying our culturally applicable ends-ways-means (EWM) model, we show how Russian and Chinese strategic cultures set distinct limits to their strategic cooperation in the Arctic. The two states’ identity-driven urge to secure and display their great power position will increasingly collide. It is therefore our prediction that Russia and China will eventually act in ways that will gradually come to undermine their strategic cooperation in the region.